PERAN MARKETING PUBLIC RELATIONS DALAM MERAWAT DAN MEMPERTAHANKAN LOYALITAS DONATUR INFAQ - Arif Zunaidi; Hendik Setiawan (Program Studi Ekonomi Syariah Fakultas Ekonomi dan Bisnis Islam IAIN Kediri, 2021)
Mojokerto City Infaq Development Institute (LPI) is a non-profit organization that manages zakat, infaq, and sadaqah funds. During competition between similar institutions, they compete to be more active and creative in designing donor- attraction strategies. Because it focuses on marketing activities, delivering products to donors, fostering trust, and maintaining good relations of donors, the marketing corporate communications strategy is important choice for donors' best interest. This is a qualitative design with a qualitative approach. According to the discussion on the subject, the application of marketing public relations strategy at LPI Mojokerto City also include promotion, advertising, creating an innovation, event, and sponsorship; public relations marketing strategy plays an important role in maintaining and maintaining donor loyalty, as evidenced by data on the increase in the number of regular donors every year.